War-related eye trauma: a study of civilian and military cases from Ukraine's ongoing conflict - Jonak, Kamil; Matysiak, Magdalena; Choragiewicz, Tomasz; Nowakowska, Dominika; Zimenkovsky, Andriy; Shybinskyi, Volodymyr; Sekh, Myroslawa; Karpiński, Robert; Podkowiński, Arkadiusz; Rejdak, Robert (Frontiers in Public Health, 2025)
Forecasts indicate a substantial increase in the occurrence of eye injuries in future armed conflicts. The Russian invasion of Ukraine, launched in February 2022, caused numerous eye injuries among civilians as well as military personnel, generating a serious epidemiological threat related to vision loss. The main goal of this study was to analyze different eye traumas in the Ukrainian population caused by hostilities, which could allow for a relative estimate of the occurrence of long-term consequences for the health care system, such as loss of vision in a large group of citizens. To assess the scale and types of eye injuries, we analyzed around 500 eye images from 470 patients who were selected because they had sustained eye injuries and were treated at a single hospital. The findings reveal that the most prevalent types of injuries were macular disorders, accounting for 49% of cases, retinal vascular changes at 30.2%, and optic nerve disorders at 22.4%. Additionally, we observed different percentages of eye injuries in the military personnel group compared to civilians. These results highlight the significant impact of eye injuries caused by war operations on the health care system. However, further research and collaborative efforts are needed to fully assess the epidemiological burden and to inform the development of effective treatment and prevention strategies.